ChemRe : learn from crisis - Yue, Tao, 1976-; Yang, Shengyun (London : Rotterdam School of Management, Erasmus University, 2012)
ChemRe EU was incorporated in 2008 in the Netherlands to support its Chinese client companies in registering chemical substances in their exports, in accordance with REACH regulations. ChemRe had hoped to use its European subsidiary to expand business beyond carrying out REACH registration tasks, but a crisis during 2009 and 2010 forced ChemRe to reassess its ambition in Europe.
Originally Published InYue, T. & Yang, S. (2012). ChemRe: Learn from Crisis. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Crisis management -- Case studies